2012
DOI: 10.1007/s13197-012-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of banana chips in polypropylene based nanocomposite packaging films

Abstract: In this study, polypropylene (PP) based nanocomposite films of 15 different compositions of nanoclay, compatibilizer and thickness were developed and used for packaging and storage of banana chips. The effect of nanocomposite films on the quality characteristics viz. moisture content (MC), water activity (WA), total color difference (TCD), breaking force (BF), free fatty acid (FFA), peroxide value(PV), total plate count (TPC) and overall acceptability score of banana chips under ambient condition at every 15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
4
15
0
3
Order By: Relevance
“…Finding of present study are in agreement with the findings of Jagdeesh et al (2007) and Purohit & Rajyalakshmi (2011). Furthermore, Manikantan et al (2014) also observed an increase in moisture of banana chips stored in polypropylene based nanocomposite packaging films.…”
Section: Physico-chemical Characteristics Of Papaya and Whole Wheat Fsupporting
confidence: 93%
See 1 more Smart Citation
“…Finding of present study are in agreement with the findings of Jagdeesh et al (2007) and Purohit & Rajyalakshmi (2011). Furthermore, Manikantan et al (2014) also observed an increase in moisture of banana chips stored in polypropylene based nanocomposite packaging films.…”
Section: Physico-chemical Characteristics Of Papaya and Whole Wheat Fsupporting
confidence: 93%
“…Decreasing trend in fat content of stored crackers may be resulted due to hydrolysis and oxidation of oil component. These results are in good agreement with Manikantan et al (2014) who noted increased free fatty acid in stored banana chips.…”
Section: Protein Contentsupporting
confidence: 92%
“…In particular, recent efforts have been focused on the development of antimicrobial and biodegradable polymer films for food packaging applications with good mechanical stability, while preserving the freshness and flavor of food products with longer shelf life to reduce food waste from spoilage (Ahmed et al 2017;Agrillo et al 2019;Huang et al 2019). Traditional petroleum-based polymeric materials, including polyethylene (Manikantan et al 2014), polycarbonate (Dhapte et al 2015), polyethylene terephthalate (Lei et al 2014), polyvinylchloride, polypropylene, polystyrene, and polyamides have typically been used as packaging materials. However, environmental concerns with respect to their production and disposal have necessitated the search for environmentally benign alternatives with comparable thermal, mechanical, and barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by [22], who stated that during storage can increase the amount of bound water which will be followed by increased water activity (aw). This was supported by [23], who stated that banana chips packed using PP then stored for 120 days experienced an increase from 0.16 to 0.60. An increase in water activity showed that the water vapor was able to permeate from outside.…”
Section: Ffa (Free Fatty Acid)mentioning
confidence: 80%